Attaining competitive advantage through effective Supply Chain Management of SMEs / Noraini Ismail and Rosmimah Mohd Roslin - Ismail, Noraini; Mohd Roslin, Rosmimah (Research Management Institute (RMI), 2008)
The inter organizational approach where relational elements are incorporated in the analysis of Supply Chain Management (SCM) of Small Medium Enterprises (SMEs) is adopted in this study. This is in line with the study's main intention of assessing the determinants or drivers for effective SCM of small businesses and their impact on the attainment of competitive advantage. The findings suggest an interesting perspective on SCM and distribution channel functions among SMEs where elements of information sharing cooperation and integration are linked to competitive advantage. The correlation amongst the three independent variables of cooperation, information sharing and integration with competitive advantage are all significant, depicting the relevancy for SMEs to focus on these relational elements. The highest correlation is noted between information sharing and integration and this definitely makes sense as SMEs strive to integrate their functions that are moving towards the attainment of common goals. Thus, the more integrated the functions amongst supply chain and distribution partners, the more likely that information would be shared amongst them. However, it is interesting to note that the predictive ability of the relational elements of cooperation, information sharing and integration on competitive advantage is not supported through the regression analysis. In other words, the existence of cooperation, information sharing and integration amongst supply chain and distribution channel members do not necessarily predict that competitive advantage will be attained. There are perhaps other factors that should be considered besides relational elements that influence competitive advantage.